A comprehensive evaluation of a two-channel portable monitor to "rule in" obstructive sleep apnea - Ward, Kim; McArdle, N.; James, A.; Bremner, A.; Simpson, L.; Cooper, M.; Palmer, L.; Fedson, A.; Mukherjee, S.; Hillman, D. (2015)
© 2015, American Academy of Sleep Medicine. All rights reserved. Study Objectives: We hypothesized that a dual-channel portable monitor (PM) device could accurately identify patients who have a high pretest probability of obstructive sleep apnea (OSA), and we evaluated factors that may contribute to variability between PM and polysomnography (PSG) results. Methods: Consecutive clinic patients (N = 104) with possible OSA completed a home PM study, a PM study simultaneous with laboratory PSG, and a second home PM study. Uniform data analysis methods were applied to both PM and PSG data. Primary outcomes of interest were the positive likelihood ratio (LR+) and sensitivity of the PM device to "rule-in" OSA, defined as an apnea-hypopnea index (AHI) = 5 events/h on PSG. Effects of different test environment and study nights, and order of study and analysis methods (manual compared to automated) on PM diagnostic accuracy were assessed. Results: The PM has adequate LR+ (4.8), sensitivity (80%), and specificity (83%) for detecting OSA in the unattended home setting when benchmarked against laboratory PSG, with better LR+ ( > 5) and specificity (100%) and unchanged sensitivity (80%) in the simultaneous laboratory comparison. There were no significant night-night (all p > 0.10) or study order effects (home or laboratory first, p = 0.08) on AHI measures. Manual PM data review improved case finding accuracy, although this was not statistically significant (all p > 0.07). Misclassification was more frequent where OSA was mild. Conclusions: Overall performance of the PM device is consistent with current recommended criteria for an "acceptable" device to confidently "rule-in" OSA (AHI = 5 events/h) in a high pretest probability clinic population. Our data support the utility of simple two-channel diagnostic devices to confirm the diagnosis of OSA in the home environment.